Between guarantees of communism and a paternalistic-market hybrid : Polish social policy at the turn of the 20th century - Księżopolski, Mirosław (Economics and Business Review, 2013)
This paper attempts to characterize the social policy model emerging in Poland during the last 23 years of transformation from socialism into a market economy with a liberal democracy. It is certainly still a model in the making, though its mixed character is already clearly visible. In order to characterize the socialist and current social policy models and to locate them in two of the mainstream social policy typologies I shall examine three key variables: (1) the principles of distribution, (2) the role of the state, (3) the degree of solidarity. The analysis is based on an assumption that similarities of the present (and also the former) Polish social policy model with social policy regimes existing in market economy countries are only superficial. Nominally similar measures or policies are based on different philosophies and serve different purposes. I aim to prove that the most characteristic feature of the dual nature of the emerging Polish social policy model is the simultaneous presence of two major currents: paternalistic and market-oriented. Therefore, the present social policy model may be described as a paternalistic-market hybrid, a term which emphasizes its very profound inconsistency. I also try to identify path-dependent processes and major path-departure changes.(original abstract)